Hyaline cartilage next generation implants from adipose‐tissue–derived mesenchymal stem cells: Comparative study on 3D‐printed polycaprolactone scaffold patterns. (27th February 2019) - Theodoridis, Konstantinos; Aggelidou, Eleni; Vavilis, Theofanis; Manthou, Maria Eleni; Tsimponis, Antonios; Demiri, Efterpi C.; Boukla, Anna; Salpistis, Christos; Bakopoulou, Athina; Mihailidis, Athanassios; Kritis, Aristeidis
Abstract: We used additive manufacturing to fabricate 3D‐printed polycaprolactone scaffolds of different geometry topologies and porosities. We present a comparative analysis of hyaline cartilage development from adipose‐tissue–derived mesenchymal stem cells (ADMSCs) on three different, newly designed scaffold geometry patterns. The first scaffold design (MESO) was based on a rectilinear layer pattern. For the second pattern (RO45), we employed a 45° rotational layer loop. The design for the third scaffold (3DHC) was a three‐dimensional honeycomb‐like pattern with a hexagonal cellular distribution and small square shapes. We examined cell proliferation, colonization, and differentiation, in relation to the scaffold's structure, as well as to the mechanical properties of the final constructs. We gave emphasis on the scaffolds, both microarchitecture and macroarchitecture, for optimal and enhanced chondrogenic differentiation, as an important parameter, not well studied in the literature. Among the three patterns tested, RO45 was the most favourable for chondrogenic differentiation, whereas 3DHC better supported cell proliferation and scaffold penetration, exhibiting also the highest rate of increase onto the mechanical properties of the final construct. We conclude that by choosing the optimal scaffold architecture, the resulting properties of our cartilaginous constructs can better approximate those of the physiological cartilage.